Binary and Ternary Nanoceramic Coatings to Protect Carbon Steel in Artificial Seawater - Rana Afif Anaee; Ahmed M. Al- Ghaban; Douaa A. Abdullah (Engineering and Technology Journal, 2016)
Binary and Ternary nanoparticles coatings have been applied on carbon steel using atomization method (cold spraying) to corrosion control in seawater. Nanoparticles were included Nano Al2O3, SiC and ZrO2. The characterization of coated surfaces has been investigated by AFM and SEM in addition to calculate the coating thickness. The binary coatings deal with 50%Al2O3-50%SiC, 50%Al2O3-ZrO2 and 50%SiC-50%ZrO2, while the ternary coating was 60%Al2O3-20%SiC-20%ZrO2. The results showed that 50%Al2O3-50%SiC had the lowest thickness and most uniform distribution in AFM and SEM due to closing in particle sizes. Corrosion test achieved to estimate the corrosion resistance, protection efficiency and porosity percentage which indicated the role of Nano particle coating to corrosion control. These data showed that the Nano 50%Al2O3-50%SiC coating had the most noble corrosion potential, lowest corrosion current density (lowest corrosion rate), highest corrosion resistance, highest efficiency 99.651 % and lowest porosity percent 1.438×10-11. Cyclic polarization also estimated to show the probability for pitting corrosion. The coating with 50%Al2O3-50%SiC gave the highest breakdown potential equal to +69mV.